Implikasies van die kommunikatiewe handelingsteorie vir In prakties-teologiese perspektief op die ekklesiologie - Dreyer, T. F. J. (Hervormde teologiese studies, 1995)
A practical theological perspective on ecclesiology as seen from the viewpoint of communicative action theory. From a practical theological perspective, this article disputes the trend in present ecclesiastical thought, abstracting a model depicting the practical functioning of the church, which is based on a single biblical metaphor. The body-of-Christ metaphor is commonly used as a church model. The eagerness to implement this construct is inspired by a paradigm shift and the incorporation of the communicative actions theory at the level of metatheory. The hypothesis of this research is that, once the matrix of this metatheory has been clearly identified, it must be ap-plied to the aspects of church life. All the biblical metaphors shedding light on the functioning of the church need reinterpretation within the framework of a postmodern society and symmetrical communicative patterns. This way of constructing an ecclesiastical perspective, would lead to a more balanced church praxis.